2018
DOI: 10.1002/cbic.201700666
|View full text |Cite
|
Sign up to set email alerts
|

Ketonization of Proline Residues in the Peptide Chains of Actinomycins by a 4‐Oxoproline Synthase

Abstract: X-type actinomycins (Acms) contain 4-hydroxyproline (Acm X ) or 4-oxoproline (Acm X ) in their β-pentapeptide lactone rings, whereas their α ring contains proline. We demonstrate that these Acms are formed through asymmetric condensation of Acm half molecules (Acm halves) containing proline with 4-hydroxyproline- or 4-oxoproline-containing Acm halves. In turn, we show-using an artificial Acm half analogue (PPL 1) with proline in its peptide chain-their conversion into the 4-hydroxyproline- and 4-oxoproline-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Previous studies demonstrated the importance of a 4-oxoproline synthase within the actinomycin BGC of S. antibioticus . This enzyme catalyzes proline oxidation in each of the actinomycin halves (prior to dimerization) to form 4-hydroxyproline or 4-oxoproline; condensation of each of the hydroxylated actinomycin halves affords actinomycin X oβ or actinomycin X 2 [42]. Within the actinomycin BGC in S. costaricanus SCSIO ZS0073, we identified a cytochrome P450 gene, acnP , that encodes a 436 aa protein.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated the importance of a 4-oxoproline synthase within the actinomycin BGC of S. antibioticus . This enzyme catalyzes proline oxidation in each of the actinomycin halves (prior to dimerization) to form 4-hydroxyproline or 4-oxoproline; condensation of each of the hydroxylated actinomycin halves affords actinomycin X oβ or actinomycin X 2 [42]. Within the actinomycin BGC in S. costaricanus SCSIO ZS0073, we identified a cytochrome P450 gene, acnP , that encodes a 436 aa protein.…”
Section: Resultsmentioning
confidence: 99%
“…Actinomycin D also contains D‐valine in the 2‐positions of its pentapeptide lactone rings, but carries proline residues in the 3‐positions of both pentapeptide lactone rings. Actinomycin D and X have a common biosynthetic origin . Moreover, actinomycin synthesis in actinomycin D‐producing S. parvulus like in actinomycin X‐producing S. antibioticus was shown to be repressible by glucose .…”
Section: Resultsmentioning
confidence: 99%
“…2 A and B). Collectively, our structure reflects an open conformation [ 18 , 31 ]] and the missing BC-loop appears to be a common characteristic for the P450 enzymes that accommodate bulky substrates [ [18] , [31] ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…, MeLeu 9 rather than MeLeu 4 is the preferred hydroxylation site) when compared with CYP-sb21 [ 7 ]. saAcmM, which was identified from S. antibioticus, catalyzes a specific hydroxylation of bicyclic chromopeptide lactones [ 31 ]. The sequence identities and similarities between CYP-sb21 and CYP-pa1, CYP-sb21 and saAcmM, and CYP-pa1 and saAcmM are 55% and 67%, 52% and 64%, and 48% and 58%, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%